MANAJEMEN PENINGKATAN MUTU PEMBELAJARAN BAHASA INGGRIS BERBASIS PROJECT BASED LEARNING (PBL) DI SMA NEGERI 1 CICALENGKA - Nining Diningsih; Tati Suminar; Ricky Yoseptr; Rita Sulastin (Al-Hasanah : Jurnal Pendidikan Agama Islam, 2021)
Behind this research is the problem of the English learning process in improving the quality of learners (Case Study On Speaking at Sma Negeri 1 Cicalengka and Sma Negeri Cikancung Bandung Regency) the english learning process has tended to be centered on teachers, generally teachers convey learning in the classroom with conventional methods and based on the results of interviews with English teachers aspects of Speaking Skill do not reach the Criteria of Completion so far. It has no effect on the quality of English learning. English learning is inseparable from the role of learning management where teachers plan, implement and evaluate various actions carried out in carrying out learning activities including utilizing various media and learning methods that make it easier for students to achieve learning goals, especially learning English on speaking aspects. To overcome this, what teachers can do is prepare learning by applying learning management. The aim of this study is to find out about learning planning using Project Learning methods in improving the speaking aspect recommending that the Project Learning method can be one of the preferred learning methods and apply it to improve students' English speaking